Modern food technologies and their impact on consumer properties of meat products - L. A. Donskova; N. M. Belyaev (Новые технологии)
Processing of food products by ionizing radiation that has been used for more than 20 years in various countries, has been legally permitted in Russia since 2017. Investigations of domestic and foreign scientists have proved the suitability of this treatment method for the purpose of sterilizing various types of products. The authors consider data on the effect of ionizing radiation on consumer properties of products to be insufficient. Sensory properties of minced poultry meat with the addition of plant powders subjected to irradiation with doses of varying power have been assessed. The results of the studies have shown significant changes in the organoleptic properties of a product when irradiated at 30 kGy and the possibility of maintaining sensory properties when irradiated with a dose of 12 kGy. The results of the research have determined the direction of further research on consumer properties, namely, nutritional value and safety of products exposed to a dose of 12 kGy.